Time Dependent Oral Microflora Changes in Removable Partial Denture Wearers (Indian Journal of Public Health Research & Development, 2021)
Background: Denture prostheses are significant interventions in oral environment for restoring lost formand function due to tooth loss. Little is known about change in microflora in removable partial denturewearers with age and time since denture delivery. Therefore, the present study was conducted to evaluateand compare the oral microbial flora pre and post insertion of removable partial denture at different timeintervals and age groups.Materials and Method: A sample of 60 patients wearing removable partial denture was included inthe study, 30 of age group 40-50 years (Group 1) and 30 of age group 50-60 years (Group 2).Sample ofunstimulated saliva was collected from the patient’s mouth from the distal most edentulous area using threesterile cotton swabs by one investigator. Colony count and identification of microorganisms was done.Results: The difference among mean colony counts between group 1 and 2 were not statistically significantat any of the three timeintervals. A statistically significant difference in colony counts was seen betweenbaseline, 1 month and 3 months in whole sample as well as both the age groups. Among various aerobicmicroorganisms, Streptococcus mitis, Diphtheroids and Candida Albicanswere the most prevailing aerobicmicro organism after 3 months of denture use, while among anaerobic organisms, Prophyromonasgingivaliswas the most prevalent microorganism after three months.Conclusion: A significant difference in colony count as well as colonizing microorganisms has been foundin the present study. This difference according to time is an important component in the affect of removablepartial denture on oral health of denture wearers. Age group was not a significant factor affecting microbialhealth in RPD wearers.
Keywords: Oral Microflora, Denture Stomatitis, Removable Partial Denture, Oral candidiasis.